L’« imaginaire sociotechnique » des publics prescripteurs sur Facebook - Daphné Duvernay; Christine Bréandon; Éric Boutin (Communication, 2016)
The authors follow users’ footprints on the of Facebook. What really interests Facebook and its partner corporations is the potential consumer that lies behind each user, whether he/she consumes online (e-consumers) or through physical distribution channels. The authors studied eight fan pages to show how the user is invited, with each footprint, to become part of an audience of influencers. The purpose is to measure the divide between the illusion of number — imagined audiences — and the actual number of contributions — real audiences.